The Hubungan Asupan Protein, Asupan Kalsium dan Riwayat Penyakit Tuberkulosis dengan Kejadian Stunting pada Balita Usia 24-59 Bulan di Desa Pulau Bayur Kuantan Singingi : The Relationship of Protein Intake, Calcium Intake and History of Tubercolosis with Incidence of Stunting in Children Aged 24-59 Months in Pulau Bayur Village, Kuantan Singingi District - Sa’adah, Nidaus; Afrinis, Nur; Isnaeni, Lira Mufti Azzahri (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2024)
One factor that influences the incidence of stunting in children aged 24-59 months is food intake, because good quality food is the main part of the growth of children under five, which certainly contains complete sources of macronutrients and micronutrients, affecting child growth. The purpose of this study was to analyze the relations of protein, calcium intake and history of Tuberculosis with the incidence of stunting in children aged 24-59 months in Pulau Bayur Village, Cerenti Health Center working area, Kuantan Singingi District. This research is a quantitative analytical study that used a cross-sectional research design. This research was conducted in Pulau Bayur village in 2-12 March 2023 with a total subject of 50 mothers of children aged 24-59 months selected using total sampling technique. Nutritional intake data were obtained through 2x24-hour food recall interviews, Tuberculosis history data were obtained through interviews, and nutritional status data were obtained through height and weight measurements. The analysis used was univariate and bivariate with Chi Square test and Fisher's Exact Test. The univariate analysis results showed that 17 children (34%) were stunted, 15 children (30%) had low protein intake, 42 children (84%) had low calcium intake, and 5 children (10%) had a history of Tuberculosis disease. Bivariate analysis results showed the protein intake (p=0.000), calcium intake (p=0.039) and history of Tuberculosis disease (p=0.003) had association with the incidence of stunting. Parents are advised to provide foods high in calcium and high in protein and maintain the children’s health so that they have normal nutritional status.